Exploring the rumen microbial function in Angus bulls with divergent residual feed intake - Sidney, Taylor; Treon, Emily; Taiwo, Godstime; Felton, Eugene; Fan, Peixin; Ogunade, Ibukun M. (Frontiers in Animal Science, 2024)
This study leverages Shotgun metagenomics to assess the rumen microbial community and functionality in Angus bulls with differing residual feed intake-expected progeny difference (RFI-EPD) values, aiming to elucidate the microbial contributions to feed efficiency. Negative RFI-EPD bulls (NegRFI: n=10; RFI-EPD= -0.3883 kg/d) and positive RFI-EPD bulls (PosRFI: n=10; RFI-EPD=0.2935 kg/d) were selected from a group of 59 Angus bulls (average body weight (BW) = 428 ± 18.8 kg; 350 ± 13.4 d of age) fed a high-forage total mixed ration after a 60-d testing period. At the end of the 60-d period, rumen fluid samples were collected for bacterial DNA extraction and subsequent shotgun metagenomic sequencing. Results of the metagenome analysis revealed greater gene richness in NegRFI bulls, compared to PosRFI. Analysis of similarity revealed a small but noticeable difference (P =0.052; R-value = 0.097) in the rumen microbial community of NegRFI and PosRFI bulls. Linear Discriminant Analysis effect size (Lefse) was utilized to identify the differentially abundant taxa. The Lefse results showed that class Fibrobacteria (LDA = 5.1) and genus Fibrobacter (LDA = 4.8) were greater in NegRFI bulls, compared to PosRFI bulls. Relative abundance of the carbohydrate-active enzymes was also compared using Lefse. The results showed greater relative abundance of glycoside hydrolases and carbohydrate-binding modules such as GH5, CBM86, CBM35, GH43, and CBM6 (LDA > 3.0) in NegRFI bulls whereas GH13 and GT2 were greater in PosRFI bulls. The distinct metabolic and microbial profiles observed in NegRFI, compared to PosRFI bulls, characterized by greater gene richness and specific taxa such as Fibrobacter, and variations in carbohydrate-active enzymes, underscore the potential genetic and functional differences in their rumen microbiome. These findings contribute to a deeper understanding of the interplay between rumen microbiota and feed efficiency in Angus bulls, opening avenues for targeted interventions and advancements in livestock management practices.